Enhancing dichromate transport and reduction via electric fields induced by photocatalysis - Chen Chen; Siyu Zhao; Bingming Zhou; Changqing Ye; Baojiang Jiang; Liping Zhang (iScience)
Summary: Mass transport is a fundamental yet often overlooked factor in influencing adsorption and photocatalytic reaction kinetics. This study examines the role of mass transport using the model system of monoclinic bismuth vanadate (BiVO4) films and potassium dichromate (K2Cr2O7) in a representative photocatalytic reaction. We show that diffusion-driven delivery of K2Cr2O7 to the BiVO4 surface increases adsorption capacity but decreases the adsorption rate constant. Notably, during the model photocatalytic reduction, long-range electric fields were observed around the illuminated BiVO4 films, a phenomenon also confirmed in a separate reaction system using TiO2 as the photocatalyst. These electric fields, distinct from the localized fields formed within heterojunctions, enhance dichromate transport by more than three orders of magnitude. This enhanced transport ensures a continuous supply of reactant to the photocatalyst, significantly improving reaction efficiency without additional energy input. These findings introduce a new strategy for optimizing photocatalytic processes, offering broad insights for advancing sustainable chemical engineering applications.